2017
DOI: 10.1002/bjs.10606
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic iron oxide nanoparticles as the sole method for sentinel node biopsy detection in patients with breast cancer

Abstract: The use of SPIO alone is a safe alternative, with results comparable to those of the standard dual technique using Tc and blue dye. The efficacy of injection in the preoperative setting simplifies logistics and improves performance. Skin staining can be prevented by a deeper peritumoral injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 30 publications
(58 reference statements)
2
68
0
Order By: Relevance
“…In those studies, patients received injections of both SPIO and 99m Tc, with or without blue dye. To address the concern of whether the results can be influenced by the presence of both tracers, a subsequent clinical trial evaluated the use of SPIO alone and compared it with 99m Tc; the results showed that the detection rates were comparable for both methods …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In those studies, patients received injections of both SPIO and 99m Tc, with or without blue dye. To address the concern of whether the results can be influenced by the presence of both tracers, a subsequent clinical trial evaluated the use of SPIO alone and compared it with 99m Tc; the results showed that the detection rates were comparable for both methods …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, magnetic methods are easier and safer, and those can replace the RI method in the future, even in facilities with radiation‐controlled areas. The price for both methods is comparable, and there is no dependence on radioactive isotope supply nor a need for radiation‐controlled areas and imaging facilities with the magnetic method. More accurate SLNB will lead to a reduction in the number of patients waiting for surgery (the wait time in Japan is around 1‐3 months), further reducing health care costs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Injection of SPIO avoids use of nuclear medicine resources and does not involve a steep learning curve. It has the additional advantage that the signal persists for up to 1 month after injection, allowing SLND at a later date, potentially after the first operation.…”
Section: Introductionmentioning
confidence: 99%